2022
DOI: 10.1021/acscatal.2c01120
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Highly Selective Surface Pathways for Methane Dry Reforming Using Mechanochemical Synthesis of Pd–CeO2

Abstract: The methane dry reforming (DRM) reaction mechanism was explored via mechanochemically prepared Pd/CeO2 catalysts (PdAcCeO2M), which yield unique Pd–Ce interfaces, where PdAcCeO2M has a distinct reaction mechanism and higher reactivity for DRM relative to traditionally synthesized impregnated Pd/CeO2 (PdCeO2IW). In situ characterization and density functional theory calculations revealed that the enhanced chemistry of PdAcCeO2M can be attributed to the presence of a carbon-modified Pd0 and Ce4+/3+ surface arran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…89-4897) emerged in 12% Pd–CeO 2 and 16% Pd–CeO 2 due to the agglomeration of Pd species. 36 Besides, the XRD patterns of CeO 2 doped with other metals are shown in Fig. S3 †…”
Section: Resultsmentioning
confidence: 99%
“…89-4897) emerged in 12% Pd–CeO 2 and 16% Pd–CeO 2 due to the agglomeration of Pd species. 36 Besides, the XRD patterns of CeO 2 doped with other metals are shown in Fig. S3 †…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the presence of CZ in the support helps to keep Rh in the metallic state and minimize carbon deposition under the reaction conditions. Jiménez et al [63] prepared a Pd/CeO 2 (PdAcCeO 2 M) catalyst using mechanical force chemistry, which exhibited a unique reaction mechanism and higher DRM reactivity and resistance to carbon deposition compared to Pd/CeO 2 (PdCeO 2 IW) catalysts synthesized via conventional impregnation. It was found that the enhanced chemistry of PdAcCeO 2 M can be attributed to the presence of carbon-modified Pd 0 and Ce 4+/3+ surface arrangements, where the unique Pd-CO intermediate species and strong Pd-CeO 2 interactions are fully activated and sustained under the reaction conditions.…”
Section: Changing the Type And Size Of Active Componentsmentioning
confidence: 99%
“…Recent studies by Jiménez et al [274] and Shen et al [245] have shed light on the potential benefits of using Pd and Pt supported over CeO 2 , respectively, using different synthesis methods. Jiménez et al [274] presented an interesting study with Pd supported over CeO 2 prepared via a mechanochemical synthesis and compared to a traditional incipient wetness impregnation synthesis. They found that the mechanochemically prepared Pd/CeO 2 catalysts presented unique PdÀ Ce interfaces, which led to a distinct reaction mechanism and higher reactivity for DRM (323 μ molH2 .g cat À 1 •s À 1 ;500 μmol CO .g cat À 1 •s À 1 ).…”
Section: Pd Pt and Ir-based Catalysts For Dry Reforming Of Methanementioning
confidence: 99%
“…The synthesis method is also an effective strategy to enhance catalyst activity for DRM. Recent studies by Jiménez et al [274] and Shen et al [245] have shed light on the potential benefits of using Pd and Pt supported over CeO 2 , respectively, using different synthesis methods. Jiménez et al [274] presented an interesting study with Pd supported over CeO 2 prepared via a mechanochemical synthesis and compared to a traditional incipient wetness impregnation synthesis.…”
Section: Pd Pt and Ir-based Catalysts For Dry Reforming Of Methanementioning
confidence: 99%